Gramsci and the Emancipation of the Subaltern Classes - Del Roio, Marcos [UNESP] (My University, 2022)
A large number of categories (re) elaborated by Gramsci in his Prison Notebooks, in recent decades in one way or another, have fallen into common use inside and outside the academy, despite having very different meanings than those used by the Sardinian revolutionary intellectual.